2016
DOI: 10.1111/een.12291
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and specificity of host‐natural enemy interactions in an urban‐rural interface

Abstract: 1. Urbanisation and agricultural intensification cause the replacement of natural ecosystems but might also create novel habitats in urban and rural ecosystems promoting some insect communities by providing food and nesting resources.2. This study investigated how host-natural enemy communities change in urban and rural landscapes and their transitional zone, the urban-rural interface, by using trap nests for cavity-nesting Hymenoptera in gardens and rapeseed fields that were either isolated or paired in the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 50 publications
0
14
1
Order By: Relevance
“…Urbanized environments might affect organisms at higher trophic levels more than their hosts or prey, particularly when they exhibit higher levels of resource specialization (Tscharntke et al 1998;Bailey et al 2005;Pereira-Peixoto et al 2016). In our study system, this may apply to insect predators but does not appear to affect the likelihood of colonies suffering parasitoid attack.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urbanized environments might affect organisms at higher trophic levels more than their hosts or prey, particularly when they exhibit higher levels of resource specialization (Tscharntke et al 1998;Bailey et al 2005;Pereira-Peixoto et al 2016). In our study system, this may apply to insect predators but does not appear to affect the likelihood of colonies suffering parasitoid attack.…”
Section: Discussionmentioning
confidence: 99%
“…Urbanization is arguably the greatest anthropogenic transformation that ecological systems experience, and while most studies of urban ecology focus on changes to the diversity and abundance of species inhabiting towns and cities, attention has only started to focus on how assemblages of interacting species are formed in urban areas, and how this is affected by the intensity of urbanization (Bennett and Gratton 2012;Quispe and Fenoglio 2015;Pereira-Peixoto et al 2016;Turrini et al 2016). Fragmentation reduces populations of native plants (Benitez-Malvido 1998;Jules 1998;Williams et al 2005), leads to decreased connectivity between vegetation patches and existing patches tend to be smaller (Medley et al 1995;McKinney 2002) and therefore of reduced quality as habitat for many animal species (Bradley and Altizer 2007;Faeth et al 2011;Turrini et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While generalist parasitoids, such as Melittobia spp. are sometimes present (e.g., Pereira‐Peixoto, Pufal, Staab, Martins, & Klein, ; Tylianakis et al., ), most parasitoids are host‐specific and only attack a single or a few closely related species at a given locality (e.g., Orlovskyte et al., ; Staab et al., ). In addition to the trophic interactions with pollen, prey and parasitoids, less well‐known interaction types were also studied with trap nests, including the plant species that leaf‐cutting bees exploit for nest construction (e.g., Torretta, Durante, Colombo, & Mabel Basilio, ) or the oil sources of neotropical oil‐collecting bees (e.g., Carvalho, Carreira, Rego, & Albuquerque, ).…”
Section: Discussion and Summary Of Literaturementioning
confidence: 99%
“…The lower abundance and species richness of insects in anthropogenic habitats were reported repeatedly from many insect assemblages (Pereira et al ., ; Cardinale, ; Geslin et al ., ; Pereira‐Peixoto et al ., ), but the observations of reverse relationships are also known, particularly in a broad range of disturbance dependent species including, for example, various aculeate Hymenoptera (Cizek et al ., ; Tropek et al ., ; Heneberg et al ., ; Bogusch et al ., ). Here, we have shown that despite most of the dominant empty snail shell adopters among insects managed to colonise the anthropogenic habitats, they failed to establish there as large populations as in the natural habitats.…”
Section: Discussionmentioning
confidence: 99%